2018
DOI: 10.1093/femsec/fiy045
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of dysbiosis in the intestinal microbial ecosystem of children and adolescents with primary hyperlipidemia and the potential role of regular hazelnut intake

Abstract: Hyperlipidemia starts at a pediatric age and represents an unquestionable risk factor for cardiovascular disease. Modulation of the intestinal microbial ecosystem (IME), in principle, can ameliorate lipid profiles. In this study, we characterized the IME of children and adolescents with primary hyperlipidemia by analyzing fecal samples through 16S rRNA gene profiling (n = 15) and short chain fatty acid (SCFA) quantification (n = 32). The same analyses were also carried out on age-matched normolipidemic control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 72 publications
1
34
0
Order By: Relevance
“…Adaptive changes of gut microbiota composition in stone formers following a high-oxalate diet could also help to explain why, in the Suryavanshi study mentioned above [44], stone formers had a high representation of oxalate-degrading species, a finding that is not coherent with the other studies listed in Table 3. A high intake of foods with elevated oxalate content, such as almonds, hazelnuts, walnuts, and pistachios, has been associated with specific changes of gut microbiota composition [110][111][112][113][114][115]. These changes are generally considered beneficial for human health and include an increased relative abundance of Lachnospira, Roseburia, Dialister, Faecalibacterium, and Lactobacillus with increased production of SCFA [110][111][112][113][114][115].…”
Section: Oxalate Intake and Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive changes of gut microbiota composition in stone formers following a high-oxalate diet could also help to explain why, in the Suryavanshi study mentioned above [44], stone formers had a high representation of oxalate-degrading species, a finding that is not coherent with the other studies listed in Table 3. A high intake of foods with elevated oxalate content, such as almonds, hazelnuts, walnuts, and pistachios, has been associated with specific changes of gut microbiota composition [110][111][112][113][114][115]. These changes are generally considered beneficial for human health and include an increased relative abundance of Lachnospira, Roseburia, Dialister, Faecalibacterium, and Lactobacillus with increased production of SCFA [110][111][112][113][114][115].…”
Section: Oxalate Intake and Microbiotamentioning
confidence: 99%
“…A high intake of foods with elevated oxalate content, such as almonds, hazelnuts, walnuts, and pistachios, has been associated with specific changes of gut microbiota composition [110][111][112][113][114][115]. These changes are generally considered beneficial for human health and include an increased relative abundance of Lachnospira, Roseburia, Dialister, Faecalibacterium, and Lactobacillus with increased production of SCFA [110][111][112][113][114][115]. The effects on Bifidobacteria and non-pathogenic Clostridia were uncertain, with some studies reporting increased representation and others reporting depletion [111,113].…”
Section: Oxalate Intake and Microbiotamentioning
confidence: 99%
“…The remaining three studies consisted of a parallel design randomised controlled trial (33) and two pre-test/post-test studies (29,30) . Studies were predominantly published in the USA (27,(31)(32)(33)(34) (n 5/8), with one being published in Germany (28) , one in Italy (30) and one in Spain (29) . Sample sizes ranged from n 15 to 194, with the proportion of female participants in each study ranging from 28 to 83 %.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…While the health benefits of nuts may in part be due to their unique nutritional composition, the exact mechanism by which nuts exert this range of beneficial health effects remains unclear. Previous trials have examined the specific microbial shifts that occur with nut consumption (27)(28)(29)(30)(31)(32)(33)(34) ; however, due to inconsistency of study findings, there is a need to evaluate the evidence base. The present systematic review aimed to synthesise the existing evidence regarding the effect of nut consumption (tree nuts and peanuts) on the gut microbiota of humans.…”
mentioning
confidence: 99%
“…The authors reported a non-significant difference in the microbial composition after the hazelnut intervention between the hyperlipidimic and control participants. In SCFAs' (measured in feces), only a significant increase in acetate concentrations was reported after the intervention in the hyperlipidimic group (59).…”
Section: Nuts and Gut Microbiotamentioning
confidence: 99%